Engineering an adhesive based on photosensitive polymer hydrogels and silver nanoparticles for wound healing. Issue 26 (10th June 2020) - Tang, Qinqing; Chen, Canwen; Jiang, Yungang; Huang, Jinjian; Liu, Ye; Nthumba, Peter M.; Gu, Guosheng; Wu, Xiuwen; Zhao, Yun; Ren, Jianan
Abstract : Adhesives developed possess a good hemostatic effect. Attractively, agents loaded into the adhesives could exert sustained excellent antibacterial properties. Abstract : Hemostasis, wound closure and prevention of infection are critical to wound healing after an injury. Skin adhesives have been used to seal incisions, thus aiding primary wound healing, as well as creating a barrier to microbes. We constructed a skin adhesive with antibacterial and hemostatic activities (AHAs) for wound management. The adhesive was made by using methacrylated hyaluronan–polyacrylamide (MHA–PAAm) hydrogels, integrated with silver nanoparticles (AgNPs) and bonded to gelatin. Because of the three-dimensional network structure of the hydrogels, nanoscale particles can be encapsulated into their voids; the AgNPs, through sustained delivery of silver ions, endow the adhesives with sustained broad-spectrum antibacterial activity. Furthermore, due to the introduction of MHA which can be crosslinked by visible light, the polyacrylamide hydrogel matrix can be formed through photo crosslinking. In addition, gelatin can be bonded to both the hydrogel matrix and host tissues because of the interaction between carboxyl and amino-moieties. Our animal studies demonstrated that the AHAs which possess tissue adhesive and antibacterial properties were easy to stretch, and were able to stop bleeding in rat tail amputation and liver injury models. AHAs enhance wound granulation tissue formation, vascular tissue formation, and collagen formation, as well as alleviate inflammation. These properties promoted wound closure in rat wound infection models, promising great potential for applying AHAs in clinical uses.